Development of remote identification the enterprises by digital technologies - Sova Olena; Ganushchak Tetiana; Khrapkina Valentyna; Onyshchenko Oksana (SHS Web of Conferences, 2021)
The article is devoted to the formulation of electronic remote identification of enterprises by digital technologies. The paper determines a practical aspect of using electronic remote identification between the bank and the organizations. The article emphasizes that BankID system has great social importance and wide practical application in Nordics and Ukraine. It is analyzed the level of Ukrainian enterprises’ computerization in various industries. The shares of some industries in the structure of the Ukrainian’s GDP with the construction of a trend line are given. Authors compare states of electronic identification in the northern countries and advantages of BankID systems. The recommendations for improvement electronic remote identification the enterprises by digital technologies are made. Keywords: digitalization of finances, finance, finance of enterprises, remote identification, digital technologies, BankID, banking.